Soil Degassing From the Xianshuihe–Xiaojiang Fault System at the Eastern Boundary of the Chuan–Dian Rhombic Block, Southwest China - Sun, Yutao; Zhou, Xiaocheng; Yan, Yucong; Li, Jingchao; Fang, Wenya; Wang, Wanli; Liu, Yongmei (Frontiers in Earth Science, 2021)
The Chuan–Dian region, situated in the middle part of the north-south seismic zone of mainland China in a highly deformed area of the eastern margin of the Tibetan Plateau, is one of the principal areas for monitoring earthquake activities in China. In this study, the geochemical characteristics of soil degassing (of CH4, H2, CO2, Rn, and Hg) and, the relationship between degassing and fault activity, were investigated in the Xianshuihe–Xiaojiang fault system (XXFS) at the eastern boundary of the Chuan–Dian rhombic block. The mean soil-gas concentrations of CH4, H2, CO2, Rn, and Hg in the XXFS were 8.1 ppm, 9.9 ppm, 0.5%, 15.1 kBq/m3 and 12.9 ng/m3, respectively. The δ13CCO2 and δ13CCH4 values of the hot-spring gases varied from −11.9‰ to −3.7‰ and −62.5‰ to 17‰, respectively. The He-C isotopic ratios indicate that the carbon in the northern and middle parts of the XXFS may have originated from deep fluids, whereas the carbon in the southern part of the XXFS is of organic origin. The high concentrations of soil gas were distributed near the faults, indicating that the faults could act as channels for gas migration. The distributions of the high soil-gas concentrations in the XXFS coincide with the highest stress and maximum strain rates, indicating that the fault activity enhanced permeability and increased the emission rates of the gases. The results of this study will be helpful for degassing in active fault zones and earthquake monitoring.